ETIKA BERPAKAIAN DI MEDIA SOSIAL YANG TERLALU TERBUKA DAN TIDAK SESUAI MENURUT SYARIAT ISLAM - Bagastavi, Fakhri Ramadhan; Atmadja, Kandhi Surya; Syahada, Muhammad Rifki; Wahyuni, Sri; Siregar, Rosmaimuna (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The ethics of dressing on social media is an important issue in the context of cultural diversityand religious values, including Islamic law. In this context, many individuals show clothesthat are too revealing and not in accordance with Islamic teachings. This study aims toanalyze the ethics of dress in social media which involves excessive exposure of the body,inappropriate clothing, and its negative effects on individuals and society. The researchmethod used in this study is a qualitative analysis of the content of clothing on social mediathat violates ethical principles and Islamic law. Through this analysis, the factors thatencourage individuals to show clothes that are too revealing and not in accordance withIslamic law are identified. The results of this study indicate that several factors influencedress ethics on social media that are not in accordance with Islamic law including theinfluence of popular culure, the urge to get attention and recognition, and the lack ofunderstanding of religiotus values.